Du Pont System Analysis to Measure Financial Performance (A Case Study on PT. Indosat TBK in 2016 – 2018) - Sri Dwiningsih; Reni Sulistyowati (Universitas Negeri Gorontalo, 2020)
Financial statements play a major role in a company which is used as decision making material and performance benchmarking. A successful company should have a good financial performance. The other way around, a company which does not have a good financial performance would impact on the company success. The study employs a ratio analysis called Du Pont System Analysis in which the analysis often applied to measure financial performance on company. Du Pont System Analysis is a combination of financial ratios from ratio activities and profitability in which the result shows interaction from assets profitability of the company. Object of the study is PT. Indosat Tbk in 2016 – 2018 as a Telecommunication company. There are 3 similiar companies used as a comparison to indicate PT Indosat Tbk position which are PT Telekomunikasi Indonesia Tbk, PT XL Axiata Tbk, and Smartfren Telecommunication Tbk. The study draws a conclusion that financial performance of PT Indosat Tbk is good compared to the other similiar companies but PT Telekomunikasi Indonesia has the best performance than the other.